Essential Metabolites of Mycobacterium tuberculosis and Their Mimics - Gyanu Lamichhane (American Society for Microbiology, 2011)
ABSTRACT An organism requires a range of biomolecules for its growth. By definition, these are essential molecules which constitute the basic metabolic requirements of an organism. A small organic molecule with chemical similarity to that of an essential metabolite may bind to the enzyme that catalyzes its production and inhibit it, likely resulting in the stasis or death of the organism. Here, we report a high-throughput approach for identifying essential metabolites of an organism using genetic and biochemical approaches and then implement computational approaches to identify metabolite mimics. We generated and genotyped 5,126 Mycobacterium tuberculosis mutants and performed a statistical analysis to determine putative essential genes. The essential molecules of M. tuberculosis were classified as products of enzymes that are encoded by genes in this list. Although incomplete, as many enzymes of M. tuberculosis have yet to be identified and characterized, this is the first report of a large number of essential molecules of the organism. We identified essential metabolites of three distinct metabolic pathways in M. tuberculosis and selected molecules with chemical similarity using cheminformatics strategies that illustrate a variety of different pharmacophores. Our approach is aimed at systematic identification of essential molecules and their mimics as a blueprint for development of effective chemical probes of M. tuberculosis metabolism, with the ultimate goal of seeking drugs that can kill this pathogen. As an illustration of this approach, we report that compounds JFD01307SC and l-methionine-S-sulfoximine, which share chemical similarity with an essential molecule of M. tuberculosis, inhibited the growth of this organism at micromolar concentrations. IMPORTANCE The estimate that more lives may have been lost in 2009 due to tuberculosis (TB) than in any year in history is alarming. Approximately 9.2 million new cases and 1.8 million deaths due to TB were reported in 2008. The widespread prevalence of Mycobacterium tuberculosis strains that are resistant to drugs currently used to treat TB means that new drugs are urgently needed to treat these infections. Here, we have identified pathways for the biosynthesis of essential metabolites and associated enzymes in M. tuberculosis using a genetics-based approach. Small molecules that mimic these essential metabolites were identified, and some of them were shown to inhibit the growth of M. tuberculosis. Therefore, we illustrate an approach based on genetics to develop inhibitors that have the potential to be advanced as candidate drugs for treating TB.